PENGARUH ZIKIR TERHADAP PENURUNAN TINGKAT KECEMASAN PADA ATLET TAEKWONDO POPDA SMA KABUPATEN DAN KOTA PEKALONGAN TAHUN 2020 - Taradipa, Doni Khairul (Unnes Journal of Sport Sciences, 2021)
Doni Khairul Taradipa. 2020. The Effect of Zikir Towards Decreased Level of Anxiety in Taekwondo Athletes at POPDA SMA Pekalongan Regency and Pekalongan City 2020. Minithesis. Department of Sports Coaching Education, Faculty of Sports Science, Universitas Negeri Semarang. Mentor: Sri Haryono, S.Pd., M.Or. The anxiety levels in Taekwondo Athletes of POPDA SMA Pekalongan Regency and Pekalongan City range from mild to severe anxiety ahead of POPDA. It is necessary to prevent athletes anxiety levels from decreasing. Therefore, the method of zikir asmaul husna was chosen with the aim to know whether or not the influence of asmaul husna dzikir on the decrease in anxiety levels of athletes. Research uses a quantitative experimental approach. Sample count of 16 athletes. Cluster random sampling techniques. Rating scale data collection technique. Hamilton Anxiety Rating Scale (HARS) research instrument. The data processing technique used is t-test data analysis using the SPSS Statistics 20 application. The results of the study showed a pre-test and post-test group experiment with a score of thitung 15,931 > ttabel 2,145 which means there is an effect of zikir on decreased anxiety levels of Taekwondo Athletes POPDA SMA Pekalongan Regency and Pekalongan City. Decreased anxiety level is 53.09%. Based on statistical analysis calculations can be concluded that there is an effect of asmaul husna zikir decrease in anxiety levels of Taekwondo Athletes POPDA SMA Pekalongan Regency and Pekalongan City. Advice: 1) asmaul husna zikir can be used as a method to lower anxiety levels for athletes, 2) the results of this study can be used as a reference for similar research and it is hoped that other researchers who will conduct similar research can be better than researchers so that it can obtain more valid results. Keywords : Zikir of asmaul husna, Decreased Level of Anxiety, Taekwondo Athletes